Load frequency control of multi‐area hybrid power system integrated with renewable energy sources utilizing FACTS & energy storage system - Dutta, Ankush; Prakash, Surya (Environmental progress & sustainable energy, 2020)
This article proposes the minimization of the frequency deviations in the three‐area hybrid power system. The application of thyristor controlled phase shifter (TCPS) and ultracapacitor (UC) is utilized on load frequency control (LFC). The quality of power supply is affected due to continuous and random changes in load during the operation of the power system. Hence, a power system control is required to maintain a continuous balance between power generation and load demand. LFC plays an important role in maintaining constant frequency and voltage in order to ensure the reliability of electric power. The proportional integral derivative (PID) is adopted for the LFC scheme. The three‐area system considered in this article is integrated with conventional and renewable energy sources such as solar, biomass, and fuel cell. TCPS connected in series with the tie‐line ensures the stabilization of the system and provides additional service like dynamic power flow control in the tie‐line and the power quality is sustained by the subordinate control of supercapacitor energy storage. The system variability is basically due to the frequency fluctuations when it is subject to the load deviations. Thus, the suppression of peak value of frequency deviation through power modulation control is the only way to reduce this problem. By using this method, the efficiency of proposed technique becomes better in deregulated environment which is accepted for the load frequency control scheme. By utilizing these technologies, the better results are obtainable than without the usage of TCPS and a supercapacitor.